Kultur Batak dalam Birokrasi Badan Kepegawaian Daerah (BKD) Kabupaten Simalungun = Batak Culture in Bureaucracy of Badan Kepegawaian Daerah (BKD) of Simalungun District - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Batak people have value system of vision, mentality and attitude which may be called as one top local culture, Dalihan Na Tolu (Somba Marhula-hula, nzanat mardongan tubu, elek marboru). Value of Dalihan Na Tolu directly gives cues in behaving. Relation of local cultural value to bureaucracy behavior which is formed from interaction between organizational characteristic and individual characteristic, will color mode of bureaucracy behavior where the culture is taking place, so there will be a new organizational culture. This study is to examine and describe relation of Batak culture values to the Bureaucracy of BKD, Simalungun District. The method used in this study was descriptive one with qualitative approach. The data used in this study were primary and secondary data. The primary data were processed from the results of observation and interview with the Bureaucracy apparatus of BKD and a number of employees of institutions other than BKD. Whereas, the secondary data were obtained from the Secretariat of BKD. Analysis unit in this study was a set of employees of BKD, Simalungun District. The results of the study indicated that the Bureaucracy culture of BKD in Simalungun District was affected by values contained in Batak culture, Dalihan Na TA. System of consanguinity, concoisme, tribe and cognation are very dominant in individual behavior in BKD. The BKD apparatus has strong tradition, belief, and values of togetherness, so that negative attitudes appear, HOTEL (Hosom, Teal, Late), it means dislike, jealousy and arrogancy which may inhibit interaction between the employees. A leader as a king (Hula-hula) is a high and authoritative power holder. The values of Dalihan Na Tolu are meant false so that Patronage System appears.